Why drills? - Parsons, R. (1996)
It is explained,why it's necessary to practice drills and which drills suit for the development of speed (for example for hurdlers) as the key to performance. With a lot of special drills. (neu publiziert in Modern Athlete & Coach, 49 (2012) 4, S. 11-14)